Alternativas de rotación de cultivos después del arroz (oryza sativa l.), en CHEPÉN – LA LIBERTAD - Becerra Quiroz, Gaby Anais (2012)
This paper describes the alternative crop rotation after rice Oryza sativa L. developed Chepén province, La Libertad. Agricultural fields were selected in the area with various alternative crops, which collected information and experiences of farmers who did crop rotation, recorded in surveys. Also used official records of the Ministry of Agriculture, Sub District Board of Irrigation Users Regulated Jequetepeque of Guadalupe. Data taken proceeded to make pictures, not applied any statistical design to be descriptive. The result was that the corn crop planted as rotation after rice, is the most profitable because the cost benefit compared to other rotational crops such as artichokes and onions among others.